The process of caring for a patient with long-term polymyositis: an individual case study - Urbańczyk, Aneta A. (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Polymyositis is a rare autoimmune disease that affects 1 in 100,000 people. It is characterized by symmetrical, progressive weakening of proximal muscles and organ dysfunction, which lead to the development of diseases, including cancer, and hinder the daily functioning of patients. This article presents the process of nursing care for a patient with long-term polymyositis, including a description of nursing problems, interventions undertaken and the results of actions. The research material is the case of a 45-year-old woman who was diagnosed with polymyositis at the age of 9. The care process was based on a nursing interview, community interview, observation, analysis of medical records, measurement of basic vital parameters, and clinical scales. The patient’s main care problems resulting from the disease process included: deficit in self-service and self-care, pain, breathing disorders, risk of skin and infectious lesions related to the use of non-invasive ventilation, risk of pressure sores as a result of long-term immobilization, malnutrition, risk of leakage of gastric/nutritional contents in the gastrostomy area, risk of skin and trophic changes in the gastrostomy area, communication disorders verbal, and the risk of depression. As a result of the therapeutic and preventive nursing activities undertaken, nursing problems were reduced or eliminated. The effectiveness and safety of the nursing care model used in the process of caring for a patient with long-term polymyositis was confirmed. All planned care goals were achieved, and the patient’s well-being and quality of life improved.